Occurrence of Cladosporium leaf blight on Rubia cordifolia in Bhadra Wildlife Sanctuary, South India - and M.B. SHIVANNA*, T.R. PARASHURAMA (Indian Phytopathology, 2013)
Rubia cordifolia L. of Rubiaceae, is a medicinally important scabrous climber. The studies were conducted to know the etiology of the disease, disease distribution pattern, disease transmission and effect of disease on secondary metabolites. Results of the study indicated that Cladosporium cladosporioides caused foliar disease in R. cordifolia in six forest regions of the sanctuary. The incidence and severity was high in Muthodi and low in Gangegiri forest regions. The pathogen was homogeneously distributed in the above forest regions. The pathogen was seed-borne and seed transmitted and could be managed by fungicide Antracol. Among the secondary metabolites tested, flavonoid and phenol contents increased with increase in infection due to C. cladosporioides, while alkaloid and steroid contents decreased.